Scaffolding Based Treffinger To Improve Students' Critical Thinking Skills - Triyanti, Putri Like; Noer, Sri Hastuti; Sutiarso, Sugeng (Journal of Education Research and Evaluation, 2021)
The purpose of this study was to improve students' critical thinking skills by using Scaffolding based Treffinger. The use of scaffolding by teachers has many forms, which can be in the form of questions, media or text-based. This article is a review of several studies / research (meta-analysis) on the use of scaffolding in learning. Scaffolding is given in full and continuously. After students get a sufficient and correct understanding, the scaffolding will be reduced and even completely eliminated. Treffinger's learning model is a learning model that trains students to find ideas in solving problems. Critical thinking is a characteristic of higher order thinking skills that are very important to be developed in school. Critical thinking skills can be trained and developed through learning that encourages students to explore, investigate, find and solve problems through learning activities in small groups. The fact is that students still have difficulty thinking critically. One way to overcome student difficulties in critical thinking is to use Scaffolding based Treffinger.